In Vitro Comparison of the Curing Depth of a Nanohybrid Resin Photoactivated by Halogen Light Versus led Light (Revista Nacional de Odontología, 2017)
Aim: To compare the curing depth of a nanohybrid resin photoactivated by halogen light versusled light according to iso 4049. Materials and methods: Current cross-sectional, descriptive, comparative laboratory method. A speci-men former was used. A strip of celluloid was placed on the base of the specimen former, on which theresin z 350 xt (3 m), shade a 2 and enamel was put. The height of the specimen former was overfilled, anda second strip of celluloid was placed on top. The resin was photoactivated by a conventional halogenlamp and a third-generation led lamp. The specimen was removed from the former and the materialin a plastic state without polymerization was removed with a spatula. The height of the cured materialwas measured with the digital micrometer (t304b.w-1220) at an accuracy of +0.01 mm. This test wasperformed three times and the average value of the curing depth was obtained. When dividing it bytwo, the curing depth was obtained according to iso 4049. Statistical normality tests (Kolmogorov-Smirnov(a) and Shapiro-Wilk) and nonparametric tests (Mann-Whitney) were performed to check if the values follow a normal distribution. The Student’s t test was used to determine if there is a statistically significant difference between the results. Results: The minimum curing depth value was obtained with the halogen lamp (2.23 mm), unlikephotoactivation by led lamp (2.32 mm). Conclusion: There are significant differences in the curing depth of a resin when photopolymerized byhalogen light versus led light.
Keywords: photoactivation; iso 4049; curing depth; nanohybrid resins